Integrating Clustering and Hybrid Nonparametric Path Modeling for Waste Management Behavior in Batu City - Moh Zhafran Hidayatulloh; Solimun Solimun; Adji Achmad Rinaldo Fernandes; Anggun Fadhila Rizqia; Fachira Haneinanda Junianto (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
This study formulates a hybrid nonparametric path analysis utilizing truncated spline-Fourier series integrated with Fuzzy C-Means clustering methodologies to investigate nonlinear behavioral patterns in community-based waste management. The model was utilized on survey data from 210 respondents in Bumiaji District, Batu City, encompassing Environmental Quality, Use of Waste Banks, Use of the 3R Principles, and Economic Benefits from Waste. Two distinct behavioral groups with varying emphasis on Use of Waste Banks and Environmental Quality were identified by the analysis. The hybrid model obtained a high coefficient of determination (0.891) and captures nonlinear relationships more successfully than the traditional linear approach. These results emphasize how crucial nonlinear behavioral dynamics are in influencing waste management behavior/decisions. The proposed framework helps local governments create more focused and efficient waste-management plans by offering a useful and adaptable analytical for understanding community behavior.